Investigating regional recharge dynamics through the use of tritium and radiocarbon isotopes to assess the hydrological resilience of groundwater in southern Africa - Van Rooyen, Jared (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.